Evaluation of a Live Attenuated Human Metapneumovirus Vaccine in Adults and Children. (21st April 2017) - Karron, Ruth A; San Mateo, Jocelyn; Wanionek, Kimberli; Collins, Peter L; Buchholz, Ursula J
Abstract: We conducted a phase I clinical trial of an experimental live attenuated recombinant human metapneumovirus (HMPV) vaccine (rHMPV-Pa) sequentially in adults, HMPV-seropositive children, and HMPV-seronegative children, the target population for vaccination. rHMPV-Pa was appropriately restricted in replication in adults and HMPV-seropositive children but was overattenuated for HMPV-seronegative children.